SYSTEMATIC LITERATURE REVIEW: SOSIAL MEDIA ORGANIK UNTUK MENDORONG BRAND AWARENESS - Agustin, Riris; Veri, Jhon (Jurnal Ekonomi dan Bisnis (EK dan BI), 2024)
Generic or organic means content that is not paid for by outside parties, is created by the brand, but can increase visibility when consumers share it with others. The aim of this research is first to analyze the potential of organic social media (SMO) to encourage brand awareness so that it can then increase sales through social media platforms. Second, what obstacles occur in organic social media marketing. By conducting a systematic literature review, this article provides aspects of organic marketing to drive consumer awareness of a brand. The method used applies Systematic Literature Review (SLR). Based on a systematic literature review, researchers found 7 final samples from 304 total articles. The findings show that organic (unpaid) social media is able to increase visibility when consumers share with others. Basically, organic social media is prioritized for awareness purposes. Organic social media, if used effectively and implementing the right strategy, can be a powerful tool for brands to expand the reach of organic posts and increase opportunities for engagement with targets.